2012
DOI: 10.1097/nmd.0b013e3182718a07
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factors Related to Suicide Attempts in Patients With Bipolar Disorder

Abstract: We compared the characteristics of patients with bipolar disorder with and without a history of suicide attempts to identify the risk factors of suicide in this disorder. Among 212 patients with bipolar disorder, 44 (21.2%) patients had histories of suicide attempts. Suicide attempters were younger and more likely to be diagnosed with bipolar II. The variables that differentiated those who did from those who did not attempt suicide included age at first contact, lifetime history of antidepressant use, major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
2
19
1
2
Order By: Relevance
“…Risk factors associated with sociodemographic components (seven studies) (Huber et al, 2014;De Abreu et al, 2012;Ruengorn et al, 2012;Algorta et al, 2011;Cassidy, 2011;Antypa et al, 2013;Ryu et al, 2010); Risk factors associated with genetic components (six studies) (Manchia et al, 2013;Sears et al, 2013;Neves et al, 2010;Magno et al, 2011;Jiménez et al, 2013;Kerner et al, 2013); Risk factors associated with Medicines and Drugs in general that interfere with bipolar disorder (eight studies) (Bellivier et al, 2011;Yoon et al, 2011;Leon et al, 2012;Arias et al, 2013;Clements et al, 2013;Finseth et al, 2012;Oquendo et al, 2010;Kenneson et al, 2013); Risk factors associated with Biological components (three studies) (Kamali et al, 2012;Evans et al, 2012;Gomes et al, 2010); Risk factors associated with Psychological causes (seven studies) (Parmentier et al, 2012;Shabani et al, 2013;Acosta et al, 2012;Song et al, 2012;Suttajit et al, 2013;Stewart et al, 2009); and Risk factors associated with components of Religious and Spiritual (three studies) components (Azorin et al, 2013;Dervic et al, 2011;. Among the 42 studies, 8 discussed about "suicide risk factors in Bipolar Affective disorder" -more broadly (Goldstein et al, 2012;Eroglu et al, 2013;Kheirabadi et al, 2012;Undurraga et al, 2012;…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Risk factors associated with sociodemographic components (seven studies) (Huber et al, 2014;De Abreu et al, 2012;Ruengorn et al, 2012;Algorta et al, 2011;Cassidy, 2011;Antypa et al, 2013;Ryu et al, 2010); Risk factors associated with genetic components (six studies) (Manchia et al, 2013;Sears et al, 2013;Neves et al, 2010;Magno et al, 2011;Jiménez et al, 2013;Kerner et al, 2013); Risk factors associated with Medicines and Drugs in general that interfere with bipolar disorder (eight studies) (Bellivier et al, 2011;Yoon et al, 2011;Leon et al, 2012;Arias et al, 2013;Clements et al, 2013;Finseth et al, 2012;Oquendo et al, 2010;Kenneson et al, 2013); Risk factors associated with Biological components (three studies) (Kamali et al, 2012;Evans et al, 2012;Gomes et al, 2010); Risk factors associated with Psychological causes (seven studies) (Parmentier et al, 2012;Shabani et al, 2013;Acosta et al, 2012;Song et al, 2012;Suttajit et al, 2013;Stewart et al, 2009); and Risk factors associated with components of Religious and Spiritual (three studies) components (Azorin et al, 2013;Dervic et al, 2011;. Among the 42 studies, 8 discussed about "suicide risk factors in Bipolar Affective disorder" -more broadly (Goldstein et al, 2012;Eroglu et al, 2013;Kheirabadi et al, 2012;Undurraga et al, 2012;…”
Section: Resultsmentioning
confidence: 98%
“…Table 1 provides an overview of all studies included in the final sample and of all data elements used during the data analysis process. Study designs included one case report (Kerner et al, 2013), seven transversal studies (Goldstein et al, 2012;Kheirabadi et al, 2012;Undurraga et al, 2012;De Abreu et al, 2012;Algorta et al, 2011;Evans et al, 2012;Gomes et al, 2010), nineteen cohort studies (Parmentier et al, 2012;Huber et al, 2014;Ruengorn et al, 2012;Etain et al, 2013;Cassidy, 2011;Baldessarini et al, 2012;Bellivier et al, 2011;Sears et al, 2013;Jiménez et al, 2013;Leon et al, 2012;Finseth et al, 2012;Oquendo et al, 2010;Kenneson et al, 2013;Gilbert et al, 2011;Shabani et al, 2013;Acosta et al, 2012;Song et al, 2012;Suttajit et al, 2013), and fifteen case-control studies (Eroglu et al, 2013;Antypa et al, 2013;Ryu et al, 2010;Manchia et al, 2013;Neves et al, 2010;Magno et al, 2011;Yoon et al, 2011;Arias et al, 2013;Clements et al, 2013;Kamali et al, 2012;de Moraes et al, 2013;Azorin et al, 2013;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, retrospective and cross sectional studies have proposed many risk factors for suicidal behavior in BD patients. These include demographic factors (female gender (Nivoli et al, 2011), age of first depressive episode (Song et al, 2012)), comorbidities (such as anxiety disorders (Baldassano, 2006), borderline personality (Neves et al, 2009), substance abuse (Finseth et al, 2012) or eating disorder (McElroy et al, 2011)), clinical features (feelings of hopelessness (Acosta et al, 2012;Johnson et al, 2005), number of mood episodes, history of suicide attempt and mixed-state or rapid cycling BD (Baldassano, 2006)), heritability, such as family history of suicide attempt (Goldstein et al, 2012), social withdrawal, stressful life events (Papolos et al, 2005). Prospective studies have shown that suicide attempts in BD patients can be predicted by: long duration of untreated illness (Altamura et al, 2010), cigarette smoking (Ostacher et al, 2009), rapid cycling (Garcia-Amador et al, 2009), early onset of Bipolar Disorder (Coryell et al, 2012), previous suicide attempt(s) (Nordstrom et al, 1995), index of depression severity (Angst et al, 2002), alcohol or other substance abuse (Preuss et al, 2003) and feelings of hopelessness (Maser et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In BD, childhood history of trauma or abuse has also been predictive of HSA [8,19,20] . Family history of HSA [2,19] , the presence of psychotic symptoms [21] , and the presence of stressors [8] have all been associated with HSA in patients with BD.…”
mentioning
confidence: 99%